Ameliorative effects of melatonin on intestinal oxidative damage in streptozotocin-induced diabetic rats - (:unkn) unknown (ISTANBUL UNIV, FAC PHARMACY, 2020)
Background and Aims: The potential therapeutic effects of melatonin on changes in intestinal tissue of diabetic rats were investigated. Methods: Male Sprague-Dawley rats were assigned into 5 groups (10 rats in each): Control, diabetes, diabetes+insulin, diabetes+melatonin, and diabetes+insulin+melatonin groups. Streptozotocin (60 mg/kg) was administered intraperitoneally to the rats to induce diabetes. At the end of 8 weeks of treatment, after blood glucose measurement and subsequent decapitation, glutathione (GSH) and matondialdehyde (MDA) levels and caspase-3, myeloperoxidase (MPO), and superoxide dismutase (SOD) activities in the intestinal tissue were investigated. Results: in diabetic animals, elevated blood glucose levels caused oxidant damage in the intestinal tissue that was demonstrated with increased MDA levels, caspase and MPO activities, and decreased GSH levels and SOD activities. Although melatonin demonstrated more significant results than insulin, separate administration of both melatonin and insulin improved the oxidative damage parameters compared to the diabetes group. In the combined treatment group, all parameters were back to control levels statistically more significant when compared with the treatment-alone. Conclusion: Melatonin has been shown to protect intestinal tissue from diabetic oxidant damage. With insulin treatment in type I diabetes, melatonin supplements may increase the quality of life through reducing complications.
Keywords: Diabetes mellitus; oxidative damage; intestine; insulin; melatonin; SUPEROXIDE-DISMUTASE ACTIVITY; CASPASE-3 ACTIVITY; STRESS; INFLAMMATION; PARAMETERS; MYELOPEROXIDASE; ACTIVATION; TISSUE; MODEL; ZINC